Physiological Diagnostic Criteria for Vascular Failure. Issue 5 (November 2018) - Tanaka, Atsushi; Tomiyama, Hirofumi; Maruhashi, Tatsuya; Matsuzawa, Yasushi; Miyoshi, Toru; Kabutoya, Tomoyuki; Kario, Kazuomi; Sugiyama, Seigo; Munakata, Masanori; Ito, Hiroshi; Ueda, Shinichiro; Vlachopoulos, Charalambos; et al.
Abstract : Supplemental Digital Content is available in the text.